PENGEMBANGAN MULTIMEDIA INTERAKTIF HPGV (HOW PLANTS GROW VISUALIZATION) UNTUK MENINGKATKAN PEMAHAMAN SISWA PADA MATA PELAJARAN IPAS MATERI PROSES PERTUMBUHAN TANAMAN DI SEKOLAH DASAR - Badruzaman, Muhammad Faishal; Atep Sujana; Isrok'atun Isrok’atun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop an interactive multimedia called HPGV (How Plants Grow Visualization) and to examine its validity, practicality, and effectiveness in improving fourth-grade elementary school students’ understanding of plant growth processes in IPAS learning. The research employed a Research and Development (R&D) method using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects were 29 fourth-grade students of SDN Sukaraja I, Sumedang Regency. Data were collected using expert validation questionnaires (material, media, and language experts), student response questionnaires, and learning achievement tests in the form of pretest and posttest. The results showed that the HPGV interactive multimedia was categorized as highly valid, with validation scores of 82.50% from material experts, 81.67% from media experts, and 94.00% from language experts. Student responses indicated that the multimedia was very practical, with all assessment aspects scoring above 80%. Furthermore, the effectiveness test revealed an improvement in students’ understanding, indicated by an increase in the average score from 65.33 in the pretest to 84.27 in the posttest, with an average N-Gain score of 0.58, which falls into the moderate category. Therefore, it can be concluded that the HPGV interactive multimedia is feasible and sufficiently effective in enhancing elementary students’ understanding of plant growth concepts in IPAS learning.